PENGEMBANGAN ALAT EKSPERIMEN PENENTUAN PERCEPATAN GRAVITASI BUMI BERDASARKAN TEORI BIDANG MIRING BERBASIS MICROCOMPUTER BASED LABORATOY (MBL) - IRNIN AGUSTINA DWI ASTUTI (Faktor Exacta, 2016)
There have been research which aims to know the development of experimental device for determineof gravity based on the theory of the inclined plane based Microcomputer Based Laboratory (MBL).Gravity is the force of attraction that occurs between all the particles having a mass in the universe. In these experiments using the tools and materials is motion detector, computer, logger pro, ruler, board track, cars, connecting cables, and beams. When the cars is dropped on an incline, then analyzed using logger pro whose data has been computerized. Method of data analysis used was linear regression analysis. The experimental results the value of the gravity in according to with the reference value in the amount of (9,895±0,529) ms-2 with a deviation of 0,91%. Key words: acceleration of gravity, logger pro, MBL, linear regression